mGlu5 Receptor Functional Interactions and Addiction - Brown, Robyn; Mustafa, Sanam; Ayoub, Mohammed; Dodd, Peter; Pfleger, Kevin; Lawrence, Andrew (Frontiers in Pharmacology, 2012)
The idea of ‘receptor mosaics’ suggests that proteins can form complex and dynamic networks, with respect to time and protein make up, which has the potential to make significant contributions to the diversity and specificity of GPCR signalling, particularly in neuropharmacology, where a few key receptors have been implicated in multiple neurological and psychiatric disorders such as addiction. Metabotropic glutamate type 5 receptors (mGlu5) have been shown to heterodimerise and form complexes with other GPCRs including adenosine A2A and dopamine D2 receptors. mGlu5-containing complexes are found in the striatum, a region of the brain known to be critical for mediating the rewarding and incentive motivational properties of drugs of abuse. Indeed, initial studies indicate a role for mGlu5-containing complexes in rewarding and conditioned effects of drugs, as well as drug-seeking behaviour. This is consistent with the substantial influence that mGlu5 complexes appear to have on striatal function, regulating both GABAergic output of striatopallidal neurons and glutamatergic input from corticostriatal afferents. Given their discrete localization, mGlu5-containing complexes represent a novel way in which to minimize the off-target effects and therefore provide us with an exciting therapeutic avenue for drug discovery efforts. Indeed, the therapeutic targeting of receptor mosaics in a tissue specific or temporal manner (for example, a sub-population of receptors in a ‘pathological state’) has the potential to dramatically reduce detrimental side effects that may otherwise impair vital brain function.